PENGARUH BELANJA MODAL, DANA PERIMBANGAN DAN PENDAPATAN ASLI DAERAH TERHADAP KINERJA KEUANGAN DAERAH KABUPATEN/KOTA PROVINSI ACEH TAHUN 2016-2020 - Novita Niswani; ikhyanuddin ikhyanuddin; Rayyan Firdaus; nurhasanah nurhasanah (Jurusan Akuntansi Fakultas Ekonomi dan Bisnis Universitas Malikussaleh, 2022)
The purpose of this study was to determine the effect of Capital Expenditure, Privileged Funds and Regional Own-source Revenue on the Financial Performance local of district/city in 2016-2020 (case study of the Aceh Provincial Goverment). The data used in this study are secondary data in the form of panel data, which is a combination of cross section data and time series data obtained from the Regional Revenue and Expenditure Budget (APBD), the number of samples in this study are 115 samples using the census sampling technique. Data analysis method in this research uses multiple linear regression analysis methods. The result of the study show that partially capital expenditure had a positive and significant effect on regional financial performance, while balancing funds and regional original income (PAD) had no significant effect on regional financial performance.